Experimental performance analysis and optimisation of medium temperature solar thermal collectors with silicon oil as a heat transfer fluid. (27th November 2011) - Nkwetta, Dan Nchelatebe; Smyth, Mervyn; Zacharopoulos, Aggelos; Hyde, Trevor
SUMMARY: Heat transfer fluids (HTFs) play an essential role in solar water heating systems by transferring collected energy from the collector, perhaps via a heat exchanger to the store. If the store is at a much higher temperature than the fluid, the store acts as a heat source, whereas the fluid acts as a coolant, thus reversing the collection process. This action must be avoided through good controls. Experimental performance analysis and comparison of three different types of solar collectors; a non‐concentrating evacuated tube heat pipe and two concentrating single‐sided and double‐sided coated evacuated tube heat pipes collectors are installed and tested using Dow‐corning 550® silicon oil as an HTF under the same operating in‐door control conditions, and results are presented in this paper. The performance of these solar collectors was determined from the overall increase in inlet and outlet fluid temperatures, overall fluid temperature differential, energy collection rate, optical efficiencies, and thermal performances. Temperature differential, energy, and collection efficiency diagrams plotted against time were used to represent and compare the solar collectors. Finally, a comparative analysis of these solar collectors using either pressurised water or Dow‐corning 550 silicon oil as HTF is presented. Copyright © 2011 John Wiley & Sons, Ltd.